If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+n-2=-5-n
We simplify the equation to the form, which is simple to understand
7+n-2=-5-n
We move all terms containing n to the left and all other terms to the right.
+1n+1n=-5-7+2
We simplify left and right side of the equation.
+2n=-10
We divide both sides of the equation by 2 to get n.
n=-5
| -16-12x=40-8x | | p+2=-2-3p | | -4p+7=7-4p | | x-77=35-6 | | 2X^2-34X+105=0 | | 0=2m+5m | | 11x-6=-39 | | 15=m-4m | | p-5-3=-9 | | 3x-7+x=10 | | -12=-5b-b | | 2(x+1)-4=5x-3(2+x) | | 7x-114=40-4x | | 9x-5x+3x-x+16=22 | | 42=28-12x | | (x^2)+6=8x | | -63-4x=135+7x | | 8=4-3b+1 | | 500+35*X=55*x | | -4n+2(-7n-5)=-7n+1 | | y^2=-4x^2+8x-3 | | X+36x=130 | | (x^2)-6x=1 | | -39-6b=-5(b+8) | | (4w^2)+12w+9=49 | | 3x=11x+25 | | -9cosx-3sinx=0 | | -9(k-1)=6-5(3k+3) | | 6(-4n-8)=96 | | -3n-5=-23 | | 8v+5=11 | | -4(-6b-4)=208 |